POST-MEIOTIC SHIFTS IN HSPA2/HSP70.2 CHAPERONE ACTIVITY DURING MOUSE SPERMATOGENESIS - Govin, Jérôme (2006)
HSPA2 (formerly HSP70.2) is a testis-specific member of the HSP70 family, known to play a critical role in the completion of meiosis during male germ cells differentiation. Although abundantly present in post-meiotic cells, its function during spermiogenesis remained obscure. Here, using a global proteomic approach to identify genome-organizing proteins in condensing spermatids, we discovered an unexpected role for HSPA2, which acquires new functions and becomes tightly associated with major spermatid DNA-packaging proteins, Transition Proteins4 (TP) 1 and 2. Hence, HSPA2 is identified here as the first TP chaperone and these data shed a new light on the yet totally unknown process of genome condensing structures assembly in spermatids.